2022
DOI: 10.1111/aswp.12253
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, noncommunicable diseases, and perceived health risks among older adults during the COVID‐19 pandemic in urban Thailand

Abstract: The COVID‐19 pandemic has had negative impacts on vulnerable populations worldwide. This study aimed to examine the association between the health worries of urban older people in Thailand and covariates related to income and non‐income poverty, noncommunicable diseases (NCDs), and metabolic risk factors (MRFs). The study utilized the 2021 Survey on Housing and Support Services for Poor Older Adults, which sampled lower‐income urban adults aged at least 55 years from five national regions. Bivariate analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…The farmers who suffer from health risk impact in deep poverty areas are more likely to be poor than those who do not suffer from the health risk. The findings are consistent with the work of Chen and Cao [ 58 ] in the context of the Chinese economy and Pothisiri, Vicerra [ 59 ] in Thailand. To avoid problematic parameter estimates of standard errors, this study re-requested the estimation of bootstrapped standard errors, and the results did not differ from model 1.…”
Section: Resultssupporting
confidence: 92%
“…The farmers who suffer from health risk impact in deep poverty areas are more likely to be poor than those who do not suffer from the health risk. The findings are consistent with the work of Chen and Cao [ 58 ] in the context of the Chinese economy and Pothisiri, Vicerra [ 59 ] in Thailand. To avoid problematic parameter estimates of standard errors, this study re-requested the estimation of bootstrapped standard errors, and the results did not differ from model 1.…”
Section: Resultssupporting
confidence: 92%
“…During the new normal of the COVID-19 era, lifestyle and health behaviors changed due to pandemic control measures, significantly affecting older adults with NCDs, particularly people living in poverty [ 42 ]. However, health behaviors and disparities in access to healthcare need to be addressed to improve HPBs among all older adults with NCDs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A global survey by the World Health Organization revealed that health treatments and prevention services for people with NCDs were significantly reduced or discontinued due to the COVID-19 pandemic [ 14 ]. A sustained and prolonged epidemic may affect HPBs, thereby diminishing the efficacy of COVID-19 controls and making it more difficult to maintain the lifestyles and well-being of older adults with NCDs [ 15 , 16 ]. These factors related to recent events have led to older adults becoming more aware of individual and public health.…”
Section: Introductionmentioning
confidence: 99%
“…Economic changes during the pandemic were prevalent among general adults and older people (10). It was found that stress and worry increased among Italians because adults had to continue working despite the pandemic (20).…”
Section: Discussionmentioning
confidence: 99%
“…This duration refers to the implementation of national lockdown measures in Thailand. Noting that the perceived risk status during the pandemic has been defined and operationalized differently based on societal factors and age groups (7,8), the set of measures for this study was evaluated for appropriateness, and it was consequently deemed suitable for older people in Thailand (10,11).…”
Section: Perceived Risk Statusmentioning
confidence: 99%